Antropologi Feminisme dan Polemik Seputar Tubuh Penari Perempuan Jaipongan menurut Perspektif Foucault - Imam Setyobudi; Mukhlas Alkaf (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
The dancers whose totally use their body and gesture explore their art-life experiences as well as to visualize their art form are always interrelated with the relation of knowledge and power. It is inclution whereas the dancers are belong to. This paper will focus on the issue of feminism in the field of the anthropological discourse as one of the Indonesian dances approach analysis. Even though it is not directly explaining how to operationalize feminism in analyzing the dances rather than serving an alternative perspective toward an older perspective in which tend to very masculine perspective.